Um nó que bruxuleia e se apaga: poesia e pensamento em Heráclito e Herberto Helder - Mariana Pereira Guida (2019)
In this dissertation we try to establish a dialogue between poetry and thought from the late work of Herberto Helder - four last books published by the author - and from the fragments bequeathed by the Presocratic thinker Heraclitus of Ephesus. We start from the premise of language as a proxy for the proximity of their discourses and adopt the metaphor as an articulating element of opposites under a unit, establishing, for exhibition purposes, metamorphosis and finitude as characteristic aspects of this articulation within the scope of textuality. We selected fire as the guiding thread of the proposed collation and from it we developed possible points of convergence between Herberto's poetry and the thought of Heraclitus regarding both metamorphosis and finitude.